DIAGNOSTIC AND PREDICTIVE POTENTIAL OF THE C-REACTIVE PROTEIN IN SERUM AND ASCITES FOR SPONTANEOUS BACTERIAL PERITONITIS IN PATIENTS WITH LIVER CIRRHOSIS AND ASCITES - Lichoska Josifovikj, Fana; Todorovska, Beti; Grivcheva Stardelova, Kalina; Genadieva Dimitrova, Magdalena; Deriban, Gjorgi; Nikolovska, Anche Volkanovska (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
Spontaneous bacterial peritonitis (SBP) in patients with liver cirrhosis is a spontaneous bacterial infection of sterile ascites fluid in the absence of intra-abdominal sources of infection or malignancy. The  purpose  of  the  study  is  to determine the diagnostic and predictive potential of CRP in serum and ascites, as an inflammatory indicator of SBP in patients with liver cirrhosis and ascites and to compare the mean values of CRP in serum and ascites in patients with and without SBP. In this prospective-observational study were included 70 patients with cirrhosis and ascites, divided into two groups, SBP and non-SBP group. Quantitative measurement of CRP in serum and ascites was determined by immunoturbidimetric method using latex particles. The average value of CRP in serum in SBP group was 35.4 ± 29.51 mg / L, and in control non-SBP group it was lower (18.6 ± 18.71 mg/L), and this difference was statistically significant for p = 0.006132. The average value of CRP in ascites in SBP group was 7.3 ± 7.2, and in non-SBP group it was lower (2.9 ± 3.1l), with statistically significant difference of p = 0.001604. ROC analysis indicates that CRP contributes to the diagnosis of SBP with 71.0% (p = 0.003) (good predictor). Univariate analysis showed that serum CRP> 6 mg / L and CRP in ascites> 6 mg / L significantly increased the chance of SBP by seven times (Exp (B) = 7,319) and three times (Exp (B) = 3,059), respectively. Our research confirmed that serum CRP is a good predictor, significantly associated with the occurrence of SBP in patients with liver cirrhosis. Keywords : SBP, C-reactive protein, ascites, liver cirrhosis https://doi.org/10.55302/JMS2142086lj